INFLUENCE OF ABSURD THEATRICAL TRADITION IN MODERN ASSAMESE DRAMA: A COMPARATIVE STUDY WITH REFERENCE TO THE PLAYS OF ARUN SHARMA - Karim, Mohammad Rezaul (Language Literacy: Journal of Linguistics, Literature, and Language Teaching, 2023)
The contemporary Assamese plays have developed as a result of numerous interwoven influences and channels. And it is clear that western influences were what shaped the Assamese plays into their perfection. After independence, Assamese writers of prose, poetry, and theatre, produced works that were on pace with the period. It demonstrated identical compositional experimentation and sociological analysis. The Assamese plays exhibit a strong western heritage from playwrights like Ibsen, Shaw, Beckett, and other absurd dramatists. A few dramatists, like Dr. Arun Sarma, Ratna Ojha, and Himendrakumar Borthakur made reflections of works of Lonesco and Beckett and despite the fact the impact of absurd dramas was not very common. In this article, the researcher investigated the works of the most renowned and esteemed Assamese playwright, Dr. Arun Sarma (1964), to emphasize the distinguishing components and similarities of Shri Nibaran Bhattacharya and Aahaar with those of absurd dramatic tropes. The researcher discovered, using the comparative technique of analysis, that, despite frequent assertions to the contrary, Aahaar has much in common with the absurdist movement, whereas Shri Nibaran Bhattacharya cannot be regarded as a fully-fledged absurd drama.